Effects of diclofenac on the gametes and embryonic development of Arbacia lixula. Issue 1 (31st December 2022) - Mauro, M.; Cammilleri, G.; Celi, M.; Cicero, A.; Arizza, V.; Ferrantelli, V.; Vazzana, M.
Abstract: Diclofenac (DCF), a non-steroidal anti-inflammatory drug (NSAID), is among the main pollutants of aquatic environments. Nevertheless, even if several authors evaluated its effects on marine organisms, no work has ever analysed its impact on the sea urchin Arbacia lixula . The purpose of this study was to analyse, for the first time, the impact of DCF at different concentrations (50 mg/l, 5 mg/l, 0.5 mg/l, 0.05 mg/l) on A. lixula embryos and gametes to indicate possible safe minimum levels of release of this drug in marine environments. Our results showed significant concentration-dependent effects on embryonic development (decrease in the number of developed embryos and increase in the quantity of degenerated eggs) and significant levels of bioaccumulation at DCF concentrations of 50 mg/l in both gametes and embryos. DCF showed a significant impact on the fertilisation of A. lixula due to its effects on gametes, confirming the possibility of environmental risk and highlighting the need to improve wastewater treatment and drug disposal processes.